The relationship between the level of religiosity and depression due to academic stress in university students - Syahla Shidqiyah; Muhammad Naufal Firdaus; Chindy Bulan; Mashita Aurellia Putri; Muhammad Rindu Fajar Islamy (Journal of Islamic Education and Innovation, 2025)
This study aims to examine the relationship between religiosity and depression caused by academic stress among university students, emphasizing the role of religiosity as an effective coping strategy. Academic stress often poses significant challenges for students, triggered by academic demands, grade expectations, and unsupportive social environments, potentially leading to depression if not properly managed. Religiosity, encompassing spiritual beliefs, religious practices, and values, is believed to provide inner peace, a sense of life purpose, and optimism, thus aiding in stress management and mental health maintenance. This study used quantitative methods approach with descriptive quantitative model, involving 41 students from various public and private universities in West Java and outside West Java who completed a psychology-based questionnaire. Findings reveal that most respondents exhibit a high level of religiosity, significantly supporting their ability to cope with academic pressures, with 56% relying on religious practices as a primary stress management strategy. The study concludes that higher religiosity levels can reduce the risk of depression, enhance emotional stability, and support academic success. These findings highlight the importance of strengthening religiosity as part of efforts to prevent and address mental health issues among university students.